Determinants of Community Preferences and Customer Loyalty at Bank Syariah Indonesia in North Sulawesi - Antuli, Sjamsuddin A. K.; Niu, Fitria Ayu Lestari; Khan, Hira (IAIN Manado, 2025)
This study aims to identify and analyze the key factors that influence customer preferences and loyalty toward Bank Syariah Indonesia (BSI) in North Sulawesi. Employing a descriptive quantitative approach, data were collected through questionnaires distributed to 52 active BSI customers across three cities: Manado, Bitung, and Kotamobagu, with respondents aged between 20 and 35 years. The research instrument underwent validity and reliability testing, yielding a Cronbach’s Alpha score of 0.969, indicating excellent internal consistency. The analysis revealed that internal bank factors, particularly the quality of employee service, including friendliness and professionalism, are the most dominant contributors to customer loyalty. External factors, such as recommendations from close associates, also play a significant role. In contrast, location and technological infrastructure, such as ATM availability, scored the lowest, suggesting areas that require improvement. The study highlights that human interaction and excellent service delivery are more decisive in fostering loyalty than physical infrastructure or rational considerations. These findings offer strategic insights for enhancing BSI services, particularly in regions with predominantly non-Muslim demographics. Practical implications include continued frontliner training, expansion of digital infrastructure and branch locations, and reinforcement of community-based marketing strategies. The study also recommends future research to explore the impact of digitalization on customer loyalty through a longitudinal approach.